Increasing Fifth Grade Students' Learning Motivation Through Learning Modules Containing Augmented Reality - Made Ratna Permata Sari; Nyoman Dantes (Universitas Pendidikan Ganesha, 2023)
The use of technology in learning activities in the field still needs to be improved. It must align with current developments prioritizing digital living using mobile and responsive educational applications. This research aims to create a learning module containing augmented reality on the human and animal respiratory systems to increase the learning motivation of fifth-grade elementary school students. This research is a type of development research using the ADDIE development model. The data collection method was a questionnaire with a rating scale instrument. The data analysis methods used are descriptive qualitative, quantitative, and inferential statistics. The results of this research show that the module developed is valid with a score of 0.95, obtaining a special index, practical with an average score of 66.07, including the very practical category, and is effectively used to increase the learning motivation of fifth-grade elementary school students with at count of more than 3,278. From the table, 1.729 with a purity of effectiveness 0.733 is classified as moderate. The learning module containing augmented reality makes it easier for students to understand information independently and can increase the learning motivation of fifth-grade elementary school students. This research implies that learning modules can help students learn independently and increase learning motivation to achieve learning goals well.